Sintering behavior, ac conductivity and dielectric relaxation of Li1.3Ti1.7Al0.3(PO4)3 NASICON compound - Zangina, Tasiu; Hassan, Jumiah; Matori, Khamirul Amin; Azis, Raba’ah Syahidah; Ahmadu, Umaru; See, Alex (Elsevier, 2016)
The phenomenon of relaxation in dielectric materials is described as one of the powerful tools to determine the behavior and properties of ion transport. The kinetics of ionic species and dipole in solid-state electrolyte are dependent on frequency, temperature, and dielectric relaxation. Li1+xTi2−xAlx(PO4)3 conducting solid state electrolyte with x = 0.3 was synthesized via conventional solid state technique using the raw materials Li2CO3, TiO2, Al2O3, and NH4H2PO4 as starting materials. TGA/DTG and X-ray diffraction measurements were carried out to study the thermal behavior and phases of the composition. It was observed from the TGA/DTA curves that there is no mass loss above 500 °C. The XRD peaks were observed to start appearing at 500 °C which corresponds to small peaks in TGA. It was also pointed out that at increasing sintering temperatures from 700 °C to 1000 °C the number of phases drastically decreased which is attributed to the complete chemical reaction. Temperature and frequency dependence of dielectric relaxation and electric modulus of the compounds were investigated at temperatures 30–230 °C and at frequencies of 40 kHz–1 MHz. The findings showed that the dielectric relaxation peaks shift to higher temperature as frequency increases and the change in ac conductivity with frequency is in agreement with Jonscher’s power law.